2006
DOI: 10.1038/sj.bmt.1705403
|View full text |Cite
|
Sign up to set email alerts
|

Adult umbilical cord blood transplantation: a comprehensive review

Abstract: Recent registry studies have established umbilical cord blood (UCB) transplantation as a safe and feasible alternative to bone marrow transplantion in adults when no sibling donor is available. There is, however, no gold standard to guide optimal treatment choices. We review here factors leading to the choice of the 'best available donor' and 'best available unit' in the case of UCB. For instance, it is clear that higher cell dose may partially overcome the negative impact of certain histocompatibility leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 59 publications
0
84
0
2
Order By: Relevance
“…[8][9][10] In addition, several registry and single institution studies have shown, both for children and adults, overall and disease-free survival rates similar to other allogeneic HSC transplants, although with different causes of mortality. [11][12][13][14][15][16][17][18] Slow and low rate of engraftment, infections during lengthy post-transplant neutropenia and toxicity of preparative regimens were recognized as factors for early TRM of CBT in large registry-based observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In addition, several registry and single institution studies have shown, both for children and adults, overall and disease-free survival rates similar to other allogeneic HSC transplants, although with different causes of mortality. [11][12][13][14][15][16][17][18] Slow and low rate of engraftment, infections during lengthy post-transplant neutropenia and toxicity of preparative regimens were recognized as factors for early TRM of CBT in large registry-based observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Recently several reviews including the clinical results of adult CBT have been published. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this review, we focus on recent results of myeloablative CBT in adults.…”
Section: Introductionmentioning
confidence: 99%
“…perfusion chambers (Koller et al 1998;Van Zant et al 1994), and stirred tanks (De Leon et al 1998;Collins et al 1998;De León et al 2001), showing advantages over static cultures. Reviews on approaches to expand HSC (Robinson et al 2005;Cabrita et al 2003) and clinical trials (Schoemans et al 2006;Devine et al 2003) have been published elsewhere. Therefore, we have focused this review on more recent biotechnological approaches aiming to increase the HSC content for transplantation.…”
Section: Hsc Culture Requirementsmentioning
confidence: 99%